WORLDVIEW AND ITS FORMATION - Abdullayeva Diyora Xabibulla qizi; Salimov Bakhriddin Lutfullaevich (Ustozlar uchun, 2025)
The article states that worldview is a system of principles, views, values, and beliefs that determine the attitude of a social group or stratum to reality, and through worldview people find their direction in life and act according to this direction. Worldview It is analyzed that the formation depends on the development of the surrounding existence.